If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -4 = -3(2 + n) Reorder the terms: -4 + n = -3(2 + n) -4 + n = (2 * -3 + n * -3) -4 + n = (-6 + -3n) Solving -4 + n = -6 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. -4 + n + 3n = -6 + -3n + 3n Combine like terms: n + 3n = 4n -4 + 4n = -6 + -3n + 3n Combine like terms: -3n + 3n = 0 -4 + 4n = -6 + 0 -4 + 4n = -6 Add '4' to each side of the equation. -4 + 4 + 4n = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 4n = -6 + 4 4n = -6 + 4 Combine like terms: -6 + 4 = -2 4n = -2 Divide each side by '4'. n = -0.5 Simplifying n = -0.5
| (x/6)+(x/3) | | k-17=-(17-k) | | (2x^2-15x-15)/(2x+3) | | -21/25y | | y-11=2(x-4) | | y-13=6(x-1) | | (x/4)*3=225 | | y-11=5(x-4) | | 3/2a+5/3a-13/6a-2/3=5/6 | | 5(r+6)=-5(r+-4) | | -31=3x+9-8 | | 0.3(y-2)=0.4(1+y) | | 20=2y-16 | | 78x^2=x-7 | | 5.7x=49.59 | | (x+3)(x-7)=(2x+5)(x-7) | | X/4=225 | | -2(k-1)=8(1+k) | | -x^2=1-2x | | 2x^2-24-6x=x^2-4x | | 3/x-x=x/10-5/2 | | 4x^2-25x=21 | | 4x-25x=21 | | 3x^2=22x+16 | | 3y/2x | | -2(k-1)=8+(1+k) | | -7/-5 | | 126=0.05x+26 | | ((9y^2)4x)12xy= | | 126.00=0.05x+26 | | 3/8+2/3 | | 5x+10y=7 |